INCLUSIVE EDUCATION IN THE BRAZILIAN PUBLIC SCHOOL SYSTEM: THE PARADOX BETWEEN ADVANCED POLICIES AND FRAGILE IMPLEMENTATION - Julia Fernanda de Lima Gomes Ilheu Campos (Revista Gênero e Interdisciplinaridade, 2026)
Inclusive education in Brazil presents a fundamental paradox: advanced legal frameworks coexist with fragile implementation. Between 2021 and 2025, enrollments of students with disabilities grew 82% (2.5 million), but 60-70% remain segregated within regular schools. Investment in education (6.5% of GDP) remains below international recommendations (8-10%), and budget allocation frequently does not prioritize inclusion. This critical narrative review analyzes the structural causes of this paradox, focusing specifically on the Brazilian context. The analysis reveals that the gap between policies and practices is deeply political and economic, not merely technical. Uncritical transfer of pedagogical models from the Global North often ignores specific Brazilian contexts. It is concluded that the realization of inclusive education requires: (1) increased investment in public education; (2) reduction of class sizes; (3) hiring of support professionals; (4) contextualized educational epistemology; (5) recognition of intersectionalities; (6) genuine participation of people with disabilities in policy decisions.